2014
DOI: 10.3233/prm-140286
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low magnitude mechanical stimulation (LMMS) on bone density in patients with Rett syndrome: A pilot and feasibility study

Abstract: PURPOSE: Low magnitude mechanical stimulation (LMMS) has been used successfully to promote bone formation in certain patient populations. This study evaluated the feasibility and effectiveness of LMMS on improving bone mineral density (BMD) in patients with Rett syndrome. METHODS: A 12-month crossover pilot study design of 6 months of intervention with LMMS and 6 months without was studied in 14 subjects divided in two subgroups. BMD was assessed using Dual Energy X-ray Absorptiometry (DXA). The levels of 25-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…It should be noted that most previous studies that reported beneficial effects of low‐intensity vibration intervention involved cohorts with severely compromised bone quality at baseline. For example, vibration interventions have been found to be beneficial in patients with renal osteodystrophy, ( 33 ) disabling conditions, ( 25 ) idiopathic scoliosis, ( 26 ) cerebral palsy, ( 27 ) Crohn's disease, ( 31 ) Rett syndrome, ( 48 ) child cancer survivors, ( 49 ) and young women (aged 15 to 20 years) with low BMD and a history of bone fracture. ( 23 ) These studies, taken together with the results of the present work, suggest that low‐intensity vibration may be best suited for individuals with compromised bone quality lacking regular stimulatory cues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that most previous studies that reported beneficial effects of low‐intensity vibration intervention involved cohorts with severely compromised bone quality at baseline. For example, vibration interventions have been found to be beneficial in patients with renal osteodystrophy, ( 33 ) disabling conditions, ( 25 ) idiopathic scoliosis, ( 26 ) cerebral palsy, ( 27 ) Crohn's disease, ( 31 ) Rett syndrome, ( 48 ) child cancer survivors, ( 49 ) and young women (aged 15 to 20 years) with low BMD and a history of bone fracture. ( 23 ) These studies, taken together with the results of the present work, suggest that low‐intensity vibration may be best suited for individuals with compromised bone quality lacking regular stimulatory cues.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recent studies have highlighted the benefit of this form of intervention, with efficacy increasing with greater adherence. ( 23,31,33,48,49 ) More reliable adherence monitoring was possible in our study because of the recording electronics inside the vibrating platforms, rather than using self‐reported device usage data. Further, routine communication between the participants and research coordinators might have positively affected adherence achieved in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Several evidences demonstrated the ability of mechanical stimuli to modulate bone formation and remodeling. Accordingly, a significant improvement in spine bone mineral density was observed in nine RTT patients enrolled in a 12-month crossover pilot study designed as a 6-month intervention period with LMMS and a 6-month period without [135]. Based on these preliminary data, LMMS could be considered as an additional feasible intervention to associate with previous reported therapeutic approaches, although further evaluation on larger cohorts of RTT patients is needed.…”
Section: Therapeutic Approaches For Bone-related Issues In Rttmentioning
confidence: 94%
“…Finally, it is worth mentioning the results of a study evaluating the effectiveness of low magnitude mechanical stimulation (LMMS) in improving bone mineral density in RTT patients [135]. Several evidences demonstrated the ability of mechanical stimuli to modulate bone formation and remodeling.…”
Section: Therapeutic Approaches For Bone-related Issues In Rttmentioning
confidence: 99%
“…A randomized controlled pilot study with WBV treatment in 20 children with CP detected improved mobility function but did not detect any positive effect on bone tissue after 6 months of treatment [21]. However, positive effects on cortical and trabecular bone have been demonstrated in a number of studies on patients with CP and Rett syndrome [22][23][24][25][26][27]. Saquetto et al [40••] published a systematic review with meta-analysis on 6 studies with 176 children with CP demonstrating increased femur BMD after WBV intervention.…”
Section: Severe Motor Disabilitiesmentioning
confidence: 99%